The fear of falls in the caregivers of institutionalized elders - Baixinho, Cristina (2022)
Aims To understand how the fear of falls emerges and manifests itself in caregivers of institutionalized elders. Method It is a qualitative study, based on the Grounded Theory and carried out with 24 informal caregivers, 5 nurses, 2 physicians and 2 directors of two Portuguese nursing homes. Data collection took place through interviews, participant observation, and documentation analysis, between October 2016 and January 2018. Data was collected and analyzed simultaneously, following the stages of open, axial, and selective coding. Results The comparative analysis of the findings identified the conceptual category "Fear of falls in the caregivers of institutionalized elders". The main category is associated with the categories: maintaining safety, hidden fear of falls, the perceived self-efficacy in the prevention of falls, falls and interpersonal relations, previous experiences, and team support. Conclusions The fear has an influence on the self-efficacy perceived in the prevention of falls; the quality of the teamwork, in turn, is affected by previous negative experiences and by the support of the team.